Enhancing Water Use Efficiency and Yield of Pomegranate Crop by Using Fish Drainage Water with Bio-Fertilizer under Drip Irrigation System - M. A. M. Moursy; Amro Negm; H. G. Ghanem; Kamal I. Wasfy (Agriculture, 2022)
Fish drainage water is a non-conventional water resource that can be exploited for irrigation due to its constituents of beneficial nutrients, signifying it as environment-friendly bio-fertilizers. Limited water resources, the elevated cost of mineral fertilizers hazards as well as attaining healthy food are of paramount significance in the agriculture sector in Egypt. The utilization of bio-fertilizers is an avenue to fulfil agricultural sustainability, production of clean crops and preservation of the soil from the accumulation of heavy metals and chemicals. Hence, this study aims to find non-conventional alternative water resources to be used for irrigation of pomegranate fruit yield. Two resources of water were utilized, and three types of bio-fertilizers were applied. Results showed that, fish drainage water increased the total yield (kg/fed) by 25.2% as compared to freshwater. Chicken manure increased the total yield (kg/fed) by 22.37 and 11.89% in comparison with cattle and compost organic fertilizer under fish drainage water, respectively. The use of chicken manure yielded the highest net return (2420.79US $/fed), while compost and cattle dung were found to be (2123.52US $/fed) and (1721.66US $/fed), respectively, under using fish drainage water. The study showed that the use of fish drainage water as an organic resource would be an alternative to commercial fertilizers, which could reduce the total cost and thus increase the net profit and yield. Less dependency of commercial fertilizer would have an impact on reducing the emissions of CO2 mitigating global warming.